Analysis of Local Politics in the Regional Head Election of Buleleng Regency, Bali - Ni Luh Ayu (Generasi Sains Indonesia, 2024)
The paper examines the workings of local politics during the Regional Head Election of Buleleng Regency, Bali with regards to the voter preference, institutional support, campaign approaches and political activity. A stratified random sampling, the quantitative research design and structured questionnaires were deployed to collect data analyzed by the descriptive and inferential statistical methods i.e., t-tests, regression analysis, ANOVA, and ANCOVA. Findings indicate that the expenditure of campaigns and the attractiveness of candidates play a great role in determining the preferences of the voters whereas satisfaction of the candidates very strongly relates with increased voter turnout. There was moderate levels of confidence in the local government especially among voters below the ages of 30 years and who were more educated and a feeling political cynicism was on the rise. Furthermore, the number of the youth who turned out to vote was very low and participation in other ways of engaging the civic life was low. These results bring to fore the essentiality of strategic campaign communique, institutional trust-building, and cult of engagement culturally embedded towards influencing electoral outcomes. This research can be used to comprehend the wider picture of subnational democratic practices and find some viable alternatives to promoting the quality of policies and inclusion characterizing local government in Indonesia.